DETEKSI DINI KESEHATAN KULIT MELALUI PENGUKURAN KADAR AIR DAN MINYAK PADA POPULASI USIA PRODUKTIF DI KELURAHAN GROGOL - Tan, Sukmawati Tansil; Santoso, Alexander Halim; Gunaidi, Farell Christian; Lucius, Steven Hizkia; Dewanto, Paulus Gegana Thery (BAMALA Institute, 2025)
Hydrated skin is a key indicator of overall skin health, as water content in the stratum corneum plays a vital role in maintaining skin barrier function. Insufficient hydration can lead to dry skin, increase susceptibility to infections, and negatively impact quality of life. This community activity aimed to assess skin water and oil levels among the productive-age population in Grogol as a preventive measure against skin dryness. The activity utilized the Plan–Do–Check–Act (PDCA) approach, which involved planning the screening, measuring skin water and oil levels, evaluating the results, and providing skin care education to participants with abnormal findings. A total of 67 participants from Grogol Village, West Jakarta, took part in this initiative. The results indicated that 11 participants (16.42%) had low oil levels and 14 participants (20.9%) had low water levels. These findings highlight the importance of maintaining proper skin hydration through adequate water intake, regular use of moisturizers, and healthy lifestyle habits. Early detection and education regarding skin hydration proved to be effective strategies in preventing dry skin and enhancing overall quality of life. Keywords: Hydration, Water Content, Oil Content, Early Detection, Dry Skin